Building Social Ethics Through Islamic Education: The Role of Schools in Promoting Human Values - Saepudin, Aep (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2021)
Islamic education plays an important role in building social ethics among students, especially through applying humanitarian values ​​in the teaching and learning process. Schools as formal educational institutions are strategic places to instill empathy, tolerance, and social responsibility among students. However, challenges such as limited resources, lack of community support, and the influence of digital media can hinder the application of these values. The purpose of this study is to explore the role of schools in promoting humanitarian values ​​through Islamic education. This study uses a qualitative approach, with data collection from previous studies and observations of interactions in the school environment. The results of the study indicate that the integration of humanitarian values ​​in the Islamic education curriculum can have a positive impact on student character. Despite various challenges, the role of teachers as role models is very important in transferring social and ethical values. With good support from the community and the surrounding environment, the application of humanitarian values ​​in schools can be optimized, producing students who are more sensitive and responsible to society. This study provides insight into the strategies needed to improve the effectiveness of humanitarian values ​​education in the context of Islamic education.